2018
DOI: 10.1190/geo2017-0492.1
|View full text |Cite
|
Sign up to set email alerts
|

Advances in 6C seismology: Applications of combined translational and rotational motion measurements in global and exploration seismology

Abstract: Over the past few decades, the potential of collocated measurements of 6C data (3C of translational and 3C of rotational motion) has been demonstrated in global seismology using high-sensitivity, observatory-based ring laser technology. Proposed applications of 6C seismology range from tomographic reconstruction of near-receiver structure to the reduction of nonuniqueness in seismic source inverse problems. Applications to exploration problems have so far been hampered by the lack of appropriate sensors, but s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 88 publications
0
36
0
Order By: Relevance
“…Displacement of a line segment δx with its end points x and x + δx in the undeformed state (light gray) being displaced by u(x) and u(x + δx) to ξ and ξ + δξ in the deformed state, respectively. The total rotation due to the displacement corresponds to the angle ω between δx and δξ modified after Reference [21].…”
Section: Theoretical Foundationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Displacement of a line segment δx with its end points x and x + δx in the undeformed state (light gray) being displaced by u(x) and u(x + δx) to ξ and ξ + δξ in the deformed state, respectively. The total rotation due to the displacement corresponds to the angle ω between δx and δξ modified after Reference [21].…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…For further information on the history of rotational seismology, we would like to refer the reader to the following reviews found in References [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Two areas of long-term vision were presented. Heiner Igel (Ludwig-Maximilians-Universitat München) outlined the status of rotational seismology, a technique that not only measures velocity/displacement in three components, but also their rotational motions (see Schmelzbach et al 2018 for a review). This allows for more accurate tilt measurements, which are important for OBS, volcano deformation and free oscillations, but also for more accurate wavefield constructions, key for seismic tomography and seismic source inversions or maximizing data in sparse networks (e.g.…”
Section: Advances On Landmentioning
confidence: 99%
“…The observation of rotations was already promoted by theoretical seismologists like Aki and Richards (2002) for a number of reasons, clearly pointing out that there is a lack of sensors recording this type of ground motion. Many developments of this new field (rotational seismology) in terms of instrumentation, theory, and applications have been documented in recent review articles (Schmelzbach et al, 2018;Igel et al, 2015; van der Baan, 2017) and two special issues (Lee et al, 2009;Igel et al, 2012). From an instrumentation point of view these developments can be subdivided into two categories: 1) the high-resolution observatory-style recording systems like ring lasers as discussed in this paper and 2) portable rotation sensors that only recently are considered fit for the specific requirements of seismic ground observations (e.g., Bernauer et al, 2012Bernauer et al, , 2018Yuan et al, 2020b;Wassermann et al, 2020).…”
Section: Introductionmentioning
confidence: 99%